What drives bidder cash reserve effects in acquisitions: Agency conflicts or precautionary motive? - Ning Gao (The University of Manchester, Manchester Business School, 2011)
A cash-rich company is less likely to be a bidder during 1994-2008 in the US, contrasting the findings based on earlier sample period. This is mainly due to the companies with high residual market-to-book ratios (i.e. the residual of the actual market-to-book ratio regressed on measures of agency conflicts). Higher bidder excess cash reserve reduces bidder return at deal announcement. The negative announcement effect is stronger for bidders of lower asset-tangibility, but insensitive to the level of agency conflicts. Post acquisition, a cash-rich bidder spends more funds on debt reduction, capital expenditure, but less on further acquisitions. Moreover, a cash-rich bidder has better operating performance when its residual market-to-book ratio is high. Our evidence suggests bidder cash reserve effects are more consistent with the precautionary motive than the agency theory. High cash reserve, to a great extent, indicates growth and overvaluation rather than agency conflicts.
Keywords: G34; D82; 330; precautionary motive of cash reserve; excess cash reserve; acquisition; announcement effect; Übernahme; Betriebliche Liquidität; Ankündigungseffekt; Prinzipal-Agent-Theorie; USA